Active counter electrode in a-SiC electrochemical metallization memory. (19th July 2017) - Morgan, K A; Fan, J; Huang, R; Zhong, L; Gowers, R; Ou, J Y; Jiang, L; De Groot, C H
Abstract: Cu/amorphous-SiC (a-SiC) electrochemical metallization memory cells have been fabricated with two different counter electrode (CE) materials, W and Au, in order to investigate the role of CEs in a non-oxide semiconductor switching matrix. In a positive bipolar regime with Cu filaments forming and rupturing, the CE influences the OFF state resistance and minimum current compliance. Nevertheless, a similarity in SET kinetics is seen for both CEs, which differs from previously published SiO2 memories, confirming that CE effects are dependent on the switching layer material or type. Both a-SiC memories are able to switch in the negative bipolar regime, indicating Au and W filaments. This confirms that CEs can play an active role in a non-oxide semiconducting switching matrix, such as a-SiC. By comparing both Au and W CEs, this work shows that W is superior in terms of a higher R OFF / R ON ratio, along with the ability to switch at lower current compliances making it a favourable material for future low energy applications. With its CMOS compatibility, a-SiC/W is an excellent choice for future resistive memory applications.